Machado-Joseph disease in Brazil: from the first descriptions to the emergence as the most common spinocerebellar ataxia - José Luiz Pedroso; Pedro Braga-Neto; João Radvany; Orlando Graziani Povoas Barsottini (Arquivos de Neuro-Psiquiatria)
Machado-Joseph disease is an autosomal dominant inherited disorder of Azorean ancestry firstly described in 1972. Since then, several Brazilian researchers have studied clinical and genetic issues related to the disease. Nowadays, Machado-Joseph disease is considered the most common spinocerebellar ataxia worldwide. Machado-Joseph disease still has no specific therapy to arrest progression, but the unclear pathophysiological mechanism, features related to genetic characteristics, phenotype variability, apparently global involvement of the nervous system in the disease and the therapeutic challenges continue to attract investigators in the field of spinocerebellar ataxias. Brazilian researchers have distinguished themselves in the ongoing investigation seeking new knowledge about Machado-Joseph disease.